Strategi Presentasi Diri Mahasiswa UINSU melalui Media Sosial Instagram (Analisis Dramaturgi Erving Goffman) - Susan Ramadhani; Abdul Rasyid (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the self-presentation strategies of students at the State Islamic University of North Sumatra (UINSU) through Instagram as a space for identity formation and self-image construction. A qualitative method with a phenomenological approach was employed, with data collected through interviews, observation, and documentation. Four students were selected as informants using purposive sampling. The findings show that students use Instagram as a front stage through strategies such as self-promotion and deliberate content selection to obtain social recognition. A gap exists between real life (back stage) and the image projected online, indicating that identity on social media is a selective construction that does not fully reflect the authentic self. Social media also encourages the formation of particular social standards that shape how students present themselves in the digital public space. These findings confirm the relevance of Erving Goffman's dramaturgical perspective in analyzing identity construction among university students